Bisphenol F exposure affects mouse oocyte in vitro maturation through inducing oxidative stress and DNA damage. Issue 6 (26th February 2022) - Ding, Zhi‐Ming; Chen, Yang‐Wu; Ahmad, Muhammad Jamil; Wang, Yong‐Sheng; Yang, Sheng‐Ji; Duan, Ze‐Qun; Liu, Ming; Yang, Cai‐Xia; Liang, Ai‐Xin; Hua, Guo‐Hua; Huo, Li‐Jun
Abstract: Bisphenol F (BPF), a substitute for bisphenol A (BPA), is progressively used to manufacture various consumer products. Despite the established reproductive toxicity of BPF, the underlying mechanisms remain to elucidate. This in‐vitro study deep in sighted the BPF toxicity on mouse oocyte meiotic maturation and quality. After treating oocytes with BPF (300 μM), the oocyte meiotic progression was blocked, accentuated by a reduced rate in the first polar body extrusion (PBE). Next, we illustrated that BPF induced α‐tubulin hyper‐acetylation disrupted the spindle assembly and chromosome alignment. Concurrently, BPF resulted in severe oxidative stress and DNA damage, which triggered the early apoptosis in mouse oocytes. Further, altered epigenetic modifications following BPF exposure were proved by increased H3K27me3 levels. Concerning the toxic effects on spindle structure, oxidative stress, and DNA damage in mouse oocytes, BPF toxicity was less severe to oocyte maturation and spindle structure than BPA and induced low oxidative stress. However, compared with BPA, oocytes treated with BPF were more prone to DNA damage, indicating not less intense or even more severe toxic effects of BPF than BPA on some aspects of oocytes maturation. In brief, the present study established that like wise to BPA, BPF could inhibit meiotic maturation and reduce oocyte quality, suggesting it is not a safe substitute for BPA.